Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Effects of clipping and shading on 15NO3− and 15NH4+ recovery by plants in grazed and ungrazed temperate grasslands - Rui Pang; Yue Sun; Xingliang Xu; Minghua Song; Hua Ouyang (Plant and Soil, 2018)

Plant organic N uptake maintains species dominance under long-term warming - Lili Jiang; Shiping Wang; Pang Zhe; Xingliang Xu; Paul Kardol; Yaoming Li; Lirong Zhang; Yanfen Wang; Zhong Lei; Zhichun Lan; Paul W. Hill; Zhenhua Zhang; et al. (Plant and Soil, 2018)

Eighty Years of Mycopathologia: A Retrospective Analysis of Progress Made in Understanding Human and Animal Fungal Pathogens - Vishnu Chaturvedi; Jean-Philippe Bouchara; Ferry Hagen; Ana Alastruey-Izquierdo; Hamid Badali; Anamelia Lorenzetti Bocca; Jose F. Cano-Lira; Cunwei Cao; Sudha Chaturvedi; Sanjay H. Chotirmall; Anne D. van Diepeningen; Jean-Pierre Gangneux; et al. (Mycopathologia, 2018)

Assessing spectral indices to estimate the fraction of photosynthetically active radiation absorbed by the vegetation canopy - Dailiang Peng; Helin Zhang; Le Yu; Mingquan Wu; Fumin Wang; Wenjiang Huang; Liangyun Liu; Rui Sun; Cunjun Li; Dacheng Wang; Fubao Xu (International Journal of Remote Sensing, 2018)

Microtremor survey and stability analysis of a soil-rock mixture landslide: a case study in Baidian town, China - Wen-wei Gao; Wei Gao; Rui-lin Hu; Pei-fen Xu; Jia-guo Xia (Landslides, 2018)

Occurrence of cucumber mosaic virus subgroup II and its genetic diversity in Sichuan, southwest of China - Chunyan Fei; Zhenpeng Xu; Lijuan Chen; Wenshan Zou; Rui Lv; Honghui Lin; Dehui Xi (Journal of Plant Pathology, 2018)

Composition of stable isotope in precipitation and its influences by different vapor sources in the eastern Qilian Mountains - Wen-xiong Jia; Xing-gang Ma; Xiu-ting Xu; Rui-feng Yuan; Dan Ding; Guo-feng Zhu (Journal of Mountain Science, 2018)

Spatial Distribution and Risk Assessment of Heavy Metals in Paddy Soils of Yongshuyu Irrigation Area from Songhua River Basin, Northeast China - Zhengwu Cui; Yang Wang; Na Zhao; Rui Yu; Guanghui Xu; Yong Yu (Chinese Geographical Science, 2018)

High-Order Statistics of Temperature Fluctuations in an Unstable Atmospheric Surface Layer over Grassland - Rui Lyu; Fei Hu; Lei Liu; Jingjing Xu; Xueling Cheng (Advances in Atmospheric Sciences, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Three-dimensional numerical modeling of gravity anomalies based on Poisson equation in space-wavenumber mixed domain - Shi-Kun Dai; Dong-Dong Zhao; Qian-Jiang Zhang; Kun Li; Qing-Rui Chen; Xu-Long Wang (Applied Geophysics, 2018)

Paleoenvironmental implications of the calcium isotope characteristics in the MD81349 from the Nintyeast Ridge in the Indian Ocean - Feng Wang; Nianqiao Fang; Chaoyong Hu; Sarah Goldsmith; Yonghang Xu; Xuan Ding; Aijun Wang; Ping Chen; Rui Bao (Acta Oceanologica Sinica, 2018)

Time is nothing: emotional consistency of autobiographical memory and its neural basis - Rui Xu; Juan Yang; Chunliang Feng; Haiyan Wu; Ruiwang Huang; Qiuli Yang; Zhihao Li; Pengfei Xu; Ruolei Gu; Yue-jia Luo (Brain Imaging and Behavior, 2018)

Structural Strength Analysis of a Tri-Floater Floating Foundation for Offshore VAWT - Liqin Liu; Haixiang Zhao; Wanhai Xu; Rui Yuan; Ying Guo (Journal of Ocean University of China, 2018)

Identification of drug target candidates of the swine pathogen Actinobacillus pleuropneumoniae by construction of protein–protein interaction network - Siqi Li; Zhipeng Su; Chengjun Zhang; Zhuofei Xu; Xiaoping Chang; Jiawen Zhu; Ran Xiao; Lu Li; Rui Zhou (Genes & Genomics, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Novel phage–host interactions and evolution as revealed by a cyanomyovirus isolated from an estuarine environment - Yongle Xu; Rui Zhang; Nannan Wang; Lanlan Cai; Yigang Tong; Qiang Sun; Feng Chen; Nianzhi Jiao (Environmental Microbiology, 2018)
Summary Cyanophages are thought to affect the community structure, population dynamics, metabolic activity and evolution of picocyanobacteria and to impact the biogeochemical cycling in aquatic ecosystems. Here, we report an estuarine Synechococcus phage, S‐CBWM1, which represents a novel viral lineage and exhibits interesting genetic features related to phage–host interactions and evolution. S‐CBWM1 encapsidates four virion‐associated proteins related to cellular metabolic regulation. Several novel auxiliary metabolic genes related to multidrug efflux, cell wall and capsule synthesis or modifications were also identified. In addition, the presence of the largest number of tRNA genes hitherto found in a phage genome may contribute to the translation efficiency of unique genes. These genomic and proteomic features of S‐CBWM1 suggested phage–host interactions involved in adaptation to eutrophic estuarine environments. Phylogenetic and metagenomic analysis of the pol γ gene in the S‐CBWM1 genome provided new insights into the evolutionary path of mitochondrial DNA polymerase gamma. The S‐CBWM1 psbA contains two group I introns, representing the first instance of multiple introns within psbA from phage. The isolation of S‐CBWM1 reveals that estuarine ecosystems contain evolutionarily novel cyanophages that drive unique phage–host interactions.

Fine mapping and identification of a novel locus qGL12.2 control grain length in wild rice (Oryza rufipogon Griff.) - Lan Qi; Yingbin Ding; Xiaoming Zheng; Rui Xu; Lizhen Zhang; Yanyan Wang; Xiaoning Wang; Lifang Zhang; Yunlian Cheng; Weihua Qiao; Qingwen Yang (Theoretical and Applied Genetics, 2018)

The Role of WD40-Repeat Protein 62 (MCPH2) in Brain Growth: Diverse Molecular and Cellular Mechanisms Required for Cortical Development - Belal Shohayeb; Nicholas Rui Lim; Uda Ho; Zhiheng Xu; Mirella Dottori; Leonie Quinn; Dominic Chi Hiung Ng (Molecular Neurobiology, 2018)

Composition and antimicrobial activity of the essential oil from the branches of Jacaranda cuspidifolia Mart. growing in Sichuan, China - Juanjuan Yuan; Tian Gan; Yingtian Liu; Hui Gao; Weifeng Xu; Tao Zhang; Rui Tan; Zhenghong Cai; Hezhong Jiang (Natural Product Research, 2018)

Effects of Rhizoma Alismatis extract on biochemical indices and adipose gene expression in oleic acid-induced hepatocyte injury in Jian carp (Cyprinus carpio var. Jian) - Jinliang Du; Rui Jia; Li-ping Cao; Weidong Ding; Pao Xu; Guojun Yin (Fish Physiology and Biochemistry, 2018)

Study of Phosphorus Removal by Using Sponge Iron Adsorption - Rui Xue; Jian Xu; Li Gu; Longhui Pan; Qiang He (Water, Air, & Soil Pollution, 2018)

A novel 76-mer peptide mimic with the synergism of superoxide dismutase and glutathione peroxidase - Yawei Xu; Yan Zhou; Rui Yin; Cheng Wang; Haijiao Chu; Junling Wang (In Vitro Cellular & Developmental Biology - Animal, 2018)

Probing the toxic mechanism of bisphenol A with acid phosphatase at the molecular level - Mengchen Xu; Rui Zhang; Wei Song; Wansong Zong; Rutao Liu (Environmental Science and Pollution Research, 2018)

Porosity model and air leakage flow field simulation of goaf based on DEM-CFD - Gang Wang; Hao Xu; Mengmeng Wu; Yue Wang; Rui Wang; Xiaoqiang Zhang (Arabian Journal of Geosciences, 2018)

Tripartite equilibrium strategy for a carbon tax setting problem in air passenger transport - Jiuping Xu; Rui Qiu; Zhimiao Tao; Heping Xie (Environmental Science and Pollution Research, 2018)

The adaptability of a wetland plant species Myriophyllum aquaticum to different nitrogen forms and nitrogen removal efficiency in constructed wetlands - Rui Wang; Na Bai; Shengjun Xu; Guoqiang Zhuang; Zhihui Bai; Zhirui Zhao; Xuliang Zhuang (Environmental Science and Pollution Research, 2018)

AngleNav: MEMS Tracker to Facilitate CT-Guided Puncture - Rui Li; Sheng Xu; William F. Pritchard; John W. Karanian; Venkatesh P. Krishnasamy; Bradford J. Wood; Zion Tsz Ho Tse (Annals of Biomedical Engineering, 2018)

Expression of BpIAA10 from Betula platyphylla (birch) is differentially regulated by different hormones and light intensities - Wendi Xu; Rui Han; Sijia Xu; Jing Jiang; Guifeng Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Physico-Chemical Properties, Aerosolization and Dissolution of Co-Spray Dried Azithromycin Particles with L-Leucine for Inhalation - Sharad Mangal; Haichen Nie; Rongkun Xu; Rui Guo; Alex Cavallaro; Dmitry Zemlyanov; Qi Zhou (Pharmaceutical Research, 2018)

The Arc Gene Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Rui Bi; Li-Li Kong; Min Xu; Guo-Dong Li; Deng-Feng Zhang; Tao Li; Yiru Fang; Chen Zhang; Buchang Zhang; Yong-Gang Yao (Molecular Neurobiology, 2018)

Up-regulation of FOS-like antigen 1 contributes to neuronal apoptosis in the cortex of rat following traumatic brain injury - Xide Xu; Rui Jiang; Peipei Gong; Qianqian Liu; Yinan Chen; Shiqiang Hou; Debin Yuan; Jiansheng Shi; Qing Lan (Metabolic Brain Disease, 2018)

Screening HCV genotype-specific epitope peptides based on conserved sequence analysis and B cell epitope prediction in HCV E2 region - Rui Hua; Xiaoyu Jiang; Lingxia Qi; Shanshan Guan; Ziyu Kuai; Yongbo Qiao; Yan Xu; Xin Gong; Yuhua Shi; Wei Kong; Junqi Niu; Hao Zhang; et al. (Immunologic Research, 2018)

Preparation of Fe-Cu-kaolinite for catalytic wet peroxide oxidation of 4-chlorophenol - Shiwei Zhou; Rui Xu; Jingzhe He; Yongchun Huang; Zejiang Cai; Minggang Xu; Zhengguo Song (Environmental Science and Pollution Research, 2018)

A single nucleotide mutation of IspF gene involved in the MEP pathway for isoprenoid biosynthesis causes yellow-green leaf phenotype in rice - Rui Huang; Yang Wang; Pingrong Wang; Chunmei Li; Fuliang Xiao; Nenggang Chen; Na Li; Caixia Li; Changhui Sun; Lihua Li; Rongjun Chen; Zhengjun Xu; et al. (Plant Molecular Biology, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)